IMPROVING THE PROFESSIONAL COMPETENCE OF STUDENTS - PHILOLOGISTS IN THE LEXICOGRAPHICAL WORKSHOP - Nikitina, Tatiana; Rogaleva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article presents the concept of improving the professional competence of students-philologists within the framework of lexicographical workshop. The potential of dictionaries as a means of forming professional competence of students-philologists, in our opinion, is not fully realized in the practice of University teaching of linguistic disciplines. Dictionary materials as a linguistic and methodological resource are used mainly in the formation and improvement of "user" skills in the field of lexicography. Students are rarely involved in the compilation of vocabulary materials. The novelty of our concept is that we offer a comprehensive improvement of professional competence of the student-philologist on lexicographical material, and not only the skills of using dictionaries. The purpose of our study, implemented on the basis of Pskov University, was to substantiate this concept, to implement it in the framework of experimental training of students-philologists, to conduct a qualitative and quantitative analysis of the results of the experiment. This article presents the theoretical foundations of the concept, shows the specific methods of formation of various components of linguistic and cultural competence of students on lexicographical material. The results of experimental training, which are also given in the article, showed a significant increase in the level of professional competence of students, and thus confirmed the effectiveness of the developed model of lexicographic workshop.